The Relationship Between Climate Factors and Leptospirosis Incidence in Central Java in 2019-2023 - Amalia Rahmi Nasution; Yulia Khairina Ashar (Karya Kesehatan Siwalima, 2025)
Each year, more than 500,000 cases of Leptospirosis are reported worldwide. This disease is spread globally, especially in humid tropical countries like Indonesia. Based on the 2023 Indonesian Health Profile, there were 2,554 cases with a CFR of 8%, and Central Java ranked second (884 cases). This study aims to determine the relationship between climate factors and the incidence of Leptospirosis in Central Java in 2019–2023. The study used a quantitative approach with an ecological study design. The sample includes data on Leptospirosis incidence, air temperature, humidity, rainfall, and sunshine duration for 60 months. This study utilized secondary data sourced from the Central Java Provincial Health Office, accessed through the Central Java PPID website, for Leptospirosis case data and the BMKG website for Climate data. Data processing was carried out using the Spearman rho correlation test method. The results are the relationship between air temperature and leptospirosis incidence (p=0.053; r=-0.251), the relationship between humidity and leptospirosis incidence (p=0.000; r=0.546), the relationship between rainfall and leptospirosis incidence (p=0.022; r=0.295), and the relationship between the duration of sunlight and leptospirosis incidence (p=0.002; r=-0.383). It was concluded that humidity, rainfall, and duration of sunlight were significantly related to leptospirosis incidence, while temperature was not. It is recommended that the government strengthen vector control, especially during the rainy season, that the community maintain personal and environmental hygiene, and that further research use a wider time and area coverage with more complex methods.